A Rock Material Micro-Strength Calibration Model for Bonded Models in Particle Flow Code. Issue 4 (October 2021) - Xia, Chang; Liu, Zhen; Zhou, Cuiying
Abstract: Distinct Element Method (DEM) can accurately simulate the large deformation and crack propagation phenomenon of soft rocks. When employing the DEM method via Particle Flow Code, an initial issue is to calibrate the parameters utilized in the model. Typically, trial and error are used to achieve calibration; however, a lack of accuracy and time and effort requirements highly threaten its application. Based on the Parallel Bonded Model (PBM), we researched the bond's failure criterion in this study. Then, the influence of micro parameters (tension strength σ c and cohesion strength c ) on the rocks' macro strength and failure mechanisms are studied. Two different test groups were considered by changing the two parameters (1): remains constant (2): σ c remains constant. The results illustrated that rock macro strength is positively correlated with its inferior PBM strength parameters. The macro strength will gradually stabilize at an upper boundary equal to 3.3 c or 3.3 σ c . With the increasing of c, the rock failure mechanisms vary from block fragmentation to shear failure. In general, the macro strength depends on the coupling effect of c and σ c expressed with an exponential relationship. Through this relationship, only two steps are enough to calibrate the two micro-strength parameters. This research proposed a new way to calibrate PBM micro-strength parameters and provided insight into building the correlation between other micromechanical parameters in the DEM.